Effect of Cartoon Shows on Kids Fashion (International Journal of Scientific Research and Management (IJSRM), 2015)
It is not necessary to say that how much the children are interested in watching cartoon and shows on T.V. Actually watching T.V. is not bad as we are living in the world of information and Technology .The Television programs are not the only reason for brighter and more empathetic generations but it is a good start. It is said that the children are being enriched in school as well as at home in front if their T.V. is an important step to making strong ,smart, caring and innovative future adults.We can easily notice the children watching Tom and Jerry, Loony Toons ,Dore-Mon, Sinchan, etc. on T.V.. Cartoons have changed drastically over the years and have lasting effects on children. Typically, children begin watching cartoons on television at an early age of six months, and by the age of two or three children become enthusiastic viewers. This paper will discuss the impact of these cartoon characters on the kids clothing behavior and will also try to explore the reasons as to why the generation is more inclined towards television and these characters